Experimental Protein-Containing Preparations Streptococcus pneumoniae, Obtained from Fresh Isolated Strains and Museum - O. M. Kukina; I. M. Gruber; N. K. Akhmatova; E. A. Kurbatova; O. V. Zhigunova; N. E. Yastrebova; I. S. Koroleva; G. V. Beloshitsky (Эпидемиология и вакцинопрофилактика)
Relevance. Vaccines based on capsular polysaccharides of pneumococci are not active against serotypes that are not included in the vaccine, non-capsulated strains and do not protect against carriage caused by other serotypes. Their use leads to the replacement of dominant serotypes of pneumococci, the appearance of highly virulent strains, changes in the microbial landscape of mucous membranes due to the appearance of other etiologically significant pathogens of respiratory tract diseases. This requires the creation of intraspecific anti-pneumococcal immunity, which will be facilitated by the development of serotype-dependent drugs, which will include protein-containing antigens of pneumococci.Objective. Study of serotype-independent activity of protein-containing antigenic components obtained from freshly isolated and archival strains of S. pneumoniae.Materials and methods. Strains of three serotypes of S. pneumoniae were used: archival strains of serotypes 6B N296, 19F N 298 and 10A N297 and freshly isolated serotypes 6B N 1121, 19F N 1055 and serogroup 10 N 1193 (from the cerebrospinal fluid of patients with purulent meningitis).. In the experimental protein-containing preparations EPCP obtained, the protein content was determined. Protective activity of EPCP and virulence of strains were determined in the model of intraperitoneal immunization and infection of BALB/c mice; LD50 was calculated using the generally accepted modified Kerber formula. The immunophenotype of lymphocytes previously isolated from donor-mice whole blood was studied by flow cytometry. Statistical analysis of the materials was carried out using parametric and nonparametric methods using the application package «Statistica for Windows», ver. 7.0 (Stat Soft, Inc); in statistical analysis, the significance level of p was assumed to be < 0.05.Results and discussion. During cultivation there was the analysis of growth dynamics showed intensive accumulation of biomass of the archival strain N296 with low virulence, and lower - by virulent strain N 1121 isolated from the patient's cerebrospinal fluid. The protein content of drugs from serotype 6B strains did not differ. The strains of other serotypes isolated during the generalized infectious process were also more virulent than the archival strain. The effect on the immunophenotype of human lymphocytes of fractions of 50-100 kDa isolated from the initial preparations obtained by culturing serotype 6B, significantly increased only under the influence of the preparation from the archival strain. In the study of protective activity of the initial preparations from strains of serotype 6B and fractions with MM 50-100 kDa only triple immunization with the initial preparation from strain N 296, at a dose of 20 micrograms of protein per mouse, led to significantly greater survival of immunized mice from infection with the newly isolated virulent strain N 1121 of homologous serotype. A fraction of 30-100 kDa provided protection of mice twice immunized with 50 mkg of protein per mouse, with a high efficacy index of 8.9, even after infection with a freshly isolated strain of heterologous S. pneumoniae serotype 3 N 10196.Conclusion. The protein-containing fraction with MM 30-100 kDa obtained from a low virulent archival strain of S. pneumoniae serotype 6B N296 possessed protective activity against a newly isolated virulent strain of heterologous serotype after double immunization. Under the action of the studied protein-containing fractions, activation of the cellular component of immune system with the involvement of innate immunity effectors and T-lymphocytes is shown. These data can be considered as a evidence for further study of EPCP to assess the possibility of their use in the design of anti-pneumococcal drug with serotype-independent protective activity.